1997
DOI: 10.1063/1.474017
|View full text |Cite
|
Sign up to set email alerts
|

A photoionization study of trifluoromethanol, CF3OH, trifluoromethyl hypofluorite, CF3OF, and trifluoromethyl hypochlorite, CF3OCl

Abstract: CF 3 OH, an important and controversial by-product of atmospheric decomposition of CF 3 CFH 2 ͑HFC-134a͒ and other hydrofluorocarbons, has been examined by photoionization mass spectrometry. The ionization onset is characterized by a broad Franck-Condon distribution, arising primarily from a substantial elongation of the CO bond upon ionization. An upper limit to the adiabatic ionization potential ͑IP͒ of р 13.08 Ϯ 0.05 eV has been established. The appearance potentials ͑APs͒ of the first two fragments have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 56 publications
5
41
0
Order By: Relevance
“…The upper bound rests on the CF 3 -I bond strength which Asher et al recently determined to high precision, D 298 (CF 3 -I) ) 227.2 ( 1.3 kJ mol -1 . 30 This is more positive than the value of 223 kJ mol -1 available to Jenkin et al 33 and therefore raises the upper bound to ∆ f H 298 (HOI).…”
Section: Product Channelsmentioning
confidence: 74%
“…The upper bound rests on the CF 3 -I bond strength which Asher et al recently determined to high precision, D 298 (CF 3 -I) ) 227.2 ( 1.3 kJ mol -1 . 30 This is more positive than the value of 223 kJ mol -1 available to Jenkin et al 33 and therefore raises the upper bound to ∆ f H 298 (HOI).…”
Section: Product Channelsmentioning
confidence: 74%
“…Continuous removal of CF 3 OH by reaction with a suitable reagent shifts the equilibrium in Equation (2) all the way to the right and allows trapping of the CF 3 OH in the form of useful derivatives. We have demonstrated this approach by conversion of the CF 3 OH into either trifluoromethyloxonium MF 6 À (M = Sb or As) salts [see above and Eq. (7)] or ethers,…”
Section: K2mentioning
confidence: 98%
“…In spite of great academic and commercial interest in -OCF 3 substituted compounds, these have been prepared exclusively by relatively cumbersome methods, such as the replacement of the doubly bonded oxygen atom in acyl fluorides by SF 4 or halogen-exchange reactions using HF at elevated temperatures and pressures and long reaction times. [3] A literature survey showed that out of 128 citations found by SciFinder for CF 3 OH, only the original synthesis reports, [2] an unsuccessful attempt to protonate CF 3 OH in HF/ SbF 5 , [4] a measurement of its UV spectrum, [5] and a study of its photoionization [6] involved the actual bulk synthesis or handling of CF 3 OH. Therefore, it was of great interest to find a more convenient access to this interesting compound to make it readily available for general syntheses.…”
mentioning
confidence: 99%
“…In addition, it plays an important role in the atmospheric degradation of CF 3 CFH 2 ͑HFC-134a͒ and other hydrofluorocarbons, and is therefore a compound that requires some attention. [24][25][26][27] Our group has recently studied cooperativity effects in cyclic trifluoromethanol trimer at the Hartree-Fock ͑HF͒ level and different basis sets. 23 In contrast to the linear structure of the methanol dimer, we found that the analogous dimer of CF 3 OH involves a secondary hydrogen bond between one of the fluorine atoms of the donor and the hydrogen atom of the acceptor molecule.…”
Section: Introductionmentioning
confidence: 99%